100,000+ baby names - Lansky, Bruce (Hachette Go, 2024)
What's new about names? The new edition of 100,000+ Baby Names by Bruce Lansky features the most up-to-date lists of names, trends, advice, and fascinating facts about names, inlcuding: hundreds of newly popular names and variations ; the atest list of top 100 names for boys and girls ; the latest naming trends what's hot and what's not ; the most rapidly rising and falling top 1,000 names ; updated lists of names to consider, including names of newly famous people and fictional characters ; the most popular gender-neutral names and their rates of use (more for boys, more for girls, or 50/50) ; new (and classic) celebrity baby names. And our list of names from around the work keeps growing! Here you'll find more than 100,000 names--complete with origins, meanings, variations, and famous namesakes.